Trees in Lao Myths and Beliefs: Roles and Symbolic Ecological Meanings through the Aspects of Folklore - Bouphapanya, Souliya; Hongsuwan, Pathom (Journal of Ecohumanism, 2024)
This paper aims to analyze the roles and symbolic ecological significance of tree motifs as depicted in Lao myths and beliefs, derived from both literary and oral traditions. The study applies the concept of roles and symbolic ecological meanings within a folkloric framework for its analysis and interpretation. The findings indicate that tree motifs in Lao myths and beliefs encompass four primary roles and symbolic ecological meanings: first, as representations of the universe and life; second, as symbols of humanity and the supernatural; third, as embodiments of fertility and prosperity; and fourth, as representations of the Buddha and the principles of Buddhist teachings. We argue that the roles and symbolic ecological meanings of trees are intricately connected to the social and cultural dimensions in both profane and sacred senses, reflecting the thought systems of the people. This connection illustrates the worldview, values, and social ideology of Laos in a compelling manner.